(untitled) (Huellas, 2022)
When the state creates urban developments, it increases land value. If the profit from this is unequally distributed, it contributes to real estate speculation. In the organization of the Metropolitan Area in Tucuman, the sector showing the greatest dynamics and growth over the last three decades is the foothills to the West, mainly in the Yerba Buena district. The opening of President Perón Avenue had a great impact on the sector, because the urban surface tripled the period of time mentioned above. The aim of this article is to analyze market values in President Perón Avenue sector and to compare them with cadastral values applied by the State. It also presents some marketing strategies applied by real state agencies to maximize their profits. This research work is bases on a blended approach, which is divided into three different stages: building a database, the analysis of data and lastly, the posing of main conclusions.